Design a Web-Based Covid 19 Assistance Information System - Rudi Ardiansyah Siregar; Muhammad Halmidar; Rohani (Institute of Computer Science (IOCS), 2021)
Covid-19 assistance is a difficult challenge to solve since it is affected by various intertwined variables, including income status, health, education, and living conditions. Beneficiary data collection must be performed correctly. As a result, the Labuhanbatu Regency Social Service should have a computerized system to monitor Covid-19 recipients based on income and living conditions. Waterfall models are used in the development of Information Systems to help the study, and the UML used is PHP programming language, MySql Database, Boostrap, and Sublime Document. As a consequence of the study's findings, Covid-19 Beneficiary Community Data Collection Based on Income and Home Conditions was implemented. This method will provide complete and correct information based on the covid-19 beneficiary community's requirements, presented in pdf format.